Research based Learning through Immersive Face to Face Interaction - Melody, Kimi; Wan Roslina, Wan Yusof; Dhana Jay, A/L Raja Gopal; Sharifah Mona, Abd Aziz Abdullah; Abdul Al-Hafiz, Ismail; Wan Sharifatun Handayani, Wan Zullkiplee; Iswan Nur Ariff, Ismail; Mardhiah, Mohd Shahabuddin (UNIMAS Publisher, 2023)
Group project for PRK1026 Chemistry II was implemented as researchbased learning through immersive face to face interaction among students and facilitator. The main activities include planning by writing proposal, conducting laboratory activities, interpretation of scientific data, followed by producing a scientific article. All pre-university students are required to complete this project as a team which cover topics related to Chemistry Learning Units in Semester Two.